Continuity, Transition and Change: Decorative Plasterwork of Late Seventeenth-Century Scotland. Issue 1 (November 2015) - Napier, William
Abstract : In the seventeenth century Scotland witnessed a flowering of decorative plasterwork. Examples range from elaborate hand-crafted ceilings in royal palaces to simple decorative casts embellishing modest rooms in town houses. This article maps the influences which impacted upon the stylistic development of this form of interior decoration during the transitional post-Restoration period.